2004
DOI: 10.1159/000080042
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Recombinant and Native Timothy Pollen (rPhl p 1, 2, 5, 6, 7, 11, 12 and nPhl p 4)- Specific IgG4 Antibodies Induced by Subcutaneous Immunotherapy with Timothy Pollen Extract in Allergic Patients

Abstract: Background: Allergen immunotherapy is a widely accepted treatment for IgE-mediated allergies. The evaluation of immunotherapy-induced IgG4 antibodies based on allergen extract is questionable because the amount of allergen-extract-specific IgG4 to individual disease-eliciting allergens cannot be determined using crude allergen extracts. In this study, we examined the specific IgE and IgG4 serum binding profiles to individual Phleum pratense allergens in grass-pollen-sensitive patients who had received grass-po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 36 publications
2
22
1
Order By: Relevance
“…In asthmatic and nonasthmatic children with house dust mites (HDM) allergy, the IgE and IgG reactivity profiles to HDM allergens, as well as IgE levels to certain allergen components, differed considerably between both groups; asthmatic children showed an expanded IgE repertoire to allergen components and increased specific IgE levels [41]. This pattern was also observed in a similar study in an Italian population [35]. One publication established an association between sensitization to minor allergens of olivetree pollen and poor tolerance to specific immunotherapy, with patients sensitized to Ole e 7 or 9 showing a 2-fold greater risk of asthmatic symptoms than patients sensitized only to Ole e 1 [42].…”
Section: Main Immunological Changes Induced By Aitmentioning
confidence: 65%
See 1 more Smart Citation
“…In asthmatic and nonasthmatic children with house dust mites (HDM) allergy, the IgE and IgG reactivity profiles to HDM allergens, as well as IgE levels to certain allergen components, differed considerably between both groups; asthmatic children showed an expanded IgE repertoire to allergen components and increased specific IgE levels [41]. This pattern was also observed in a similar study in an Italian population [35]. One publication established an association between sensitization to minor allergens of olivetree pollen and poor tolerance to specific immunotherapy, with patients sensitized to Ole e 7 or 9 showing a 2-fold greater risk of asthmatic symptoms than patients sensitized only to Ole e 1 [42].…”
Section: Main Immunological Changes Induced By Aitmentioning
confidence: 65%
“…The detection of specific serum IgG4 antibodies a few weeks after the start of AIT was a valuable tool to estimate the presence of relevant allergens in the immunotherapeutic allergen extract [35]. It has been shown that IgE response against grass pollen molecules can start years before symptoms onset as a weak sensitization phenomenon.…”
Section: Main Immunological Changes Induced By Aitmentioning
confidence: 99%
“…Recombinant allergens have been used for the in vitro diagnosis of grass (1206,1207,1213,1246,1247), birch and Fagaleae (1248)(1249)(1250)(1251)(1252)(1253), Oleaceae (1199,1254), pollens or mites (1255)(1256)(1257). A single recombinant allergen or a combination of a few major recombinant allergens can substitute the crude extract for in vitro diagnostic purposes (1258,1259).…”
Section: In Vitro Testsmentioning
confidence: 99%
“…Often treatment-induced increases of allergen-specific IgE are moderate and might be overcome by the induction of high levels of allergen-specific IgG [21,[48][49][50][51][52][53]. Treatmentinduced increases of allergen-specific IgE up to the fourfold baseline levels have been observed in a recent SLIT study whereas allergen-specific IgG remained very low [44,54].…”
Section: Factors Limiting the Broad Application Of Allergen-specific mentioning
confidence: 99%